Accelerated ultraviolet aging of structural and luminescent properties of the ureasil-polyether hybrid materials U-PEO:Eu3+ and U-PPO:Eu3+ - Palácio, Gustavo [UNESP]; Boyer, Damien; Therias, Sandrine; Pulcinelli, Sandra H. [UNESP]; Mahiou, Rachid; Chadeyron, Geneviève; Santilli, Celso V. [UNESP] (Elsevier, 2019)
In this paper, we evaluate the role played by the polyether type and chain length on the complexation of Eu3+ by the urea group of siloxane-polyether organic-inorganic hybrid materials based on polyethylene oxide (U-PEO, mw = 1900 g mol−1) and polypropylene oxide (U-PPO, mw = 230, 2000, and 4000 g mol−1). Investigation was made of the effect of the photooxidation of the PEO and PPO chains, induced by artificially accelerated ultraviolet aging (λ ≥ 300 nm), with the decomplexation of Eu3+ from the urea-polyether array. Fourier transform infrared (FTIR) and photoluminescence (PL) spectra evidenced loss of the ligand-to-metal charge transfer (LMCT) when the Eu3+ cations were unable to disrupt the strong hydrogen-bonded urea/urea aggregates formed using shorter U-PPO chains (230 g mol−1) or semicrystalline U-PEO (1900 g mol−1). FTIR analysis showed that formate was the main photoproduct formed continuously during the artificial ultraviolet aging of U-PEO (1900 g mol−1) and U-PPO (2000 g mol−1), with concomitant decreases of Eu3+ complexed to urea bridges, spatially correlated siloxane nodes, and the Judd-Ofelt parameter Ω2 (R). The kinetics of all these parameters were described by exponential laws with comparable time constants, evidencing the sensitivity of the Eu3+ photoluminescence to the elimination/formation of the hydrogen-bonded urea-polyether array during the photooxidation of PPO chains. In the case of U-PEO:Eu3+, different time constant values were observed, indicating the existence of a faster process governed by the facilitated transport of the oxidative species through the amorphous moieties of the semicrystalline U-PEO. This sensitivity of structural and PL properties arising from the photoinduced degradation of ureasil-polyether films can be exploited in the fabrication of new transparent, flexible, and biocompatible UV dosimeters and sensors.
Keywords: Organic-inorganic hybrid materials; Photoluminescence; Photooxidation; Polyether; Sol-gel